Exploring atmospheric radon with airborne gamma-ray spectroscopy. (December 2017) - Baldoncini, Marica; Albéri, Matteo; Bottardi, Carlo; Minty, Brian; Raptis, Kassandra G.C.; Strati, Virginia; Mantovani, Fabio
Abstract: 222 Rn is a noble radioactive gas produced along the 238 U decay chain, which is present in the majority of soils and rocks. As 222 Rn is the most relevant source of natural background radiation, understanding its distribution in the environment is of great concern for investigating the health impacts of low-level radioactivity and for supporting regulation of human exposure to ionizing radiation in modern society. At the same time, 222 Rn is a widespread atmospheric tracer whose spatial distribution is generally used as a proxy for climate and pollution studies. Airborne gamma-ray spectroscopy (AGRS) always treated 222 Rn as a source of background since it affects the indirect estimate of equivalent 238 U concentration. In this work the AGRS method is used for the first time for quantifying the presence of 222 Rn in the atmosphere and assessing its vertical profile. High statistics radiometric data acquired during an offshore survey are fitted as a superposition of a constant component due to the experimental setup background radioactivity plus a height dependent contribution due to cosmic radiation and atmospheric 222 Rn. The refined statistical analysis provides not only a conclusive evidence of AGRS 222 Rn detection but also a (0.96 ± 0.07) Bq/m 3 222 Rn concentration and a (1318 ± 22) m atmospheric layer depth fully compatible with literature data. Graphical abstract: Highlights: An airborne gamma-ray survey over the sea up to 3 km altitude is presented. A theoretical model of the count rate in the presence of radon is developed. The concentration and vertical distribution of atmospheric radon is investigated. Airborne gamma-ray spectroscopy has high potential in measuring atmospheric radon.